2004
DOI: 10.4269/ajtmh.2004.70.83
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infection With Waterborne Pathogens: A Seroepidemiologic Study in Children 6–36 Months Old in San Juan Sacatepequez, Guatemala

Abstract: Water and sanitation interventions in developing countries have historically been difficult to evaluate. We conducted a seroepidemiologic study with the following goals: 1) to determine the feasibility of using antibody markers as indicators of waterborne pathogen infection in the evaluation of water and sanitation intervention projects; 2) to characterize the epidemiology of waterborne diarrheal infections in rural Guatemala, and 3) to measure the age-specific prevalence of antibodies to waterborne pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 20 publications
1
34
1
2
Order By: Relevance
“…from a study in rural China, and from a study in Guatemala (37,43,47). However, the results observed for the 74 children in our study must be interpreted with some caution, as they may not be representative of the entire birth cohort.…”
mentioning
confidence: 43%
“…from a study in rural China, and from a study in Guatemala (37,43,47). However, the results observed for the 74 children in our study must be interpreted with some caution, as they may not be representative of the entire birth cohort.…”
mentioning
confidence: 43%
“…Steinberg and others studied seroprevalence of several waterborne infections in infants 6-36 months old in Guatemala (Steinberg et al 2004). They used the second generation ELISA (see below, Priest et al 2001) to measure…”
Section: Mironmentioning
confidence: 99%
“…Populations in developing regions of the world, like Haiti and Peru, are certainly exposed to Cryptosporidium at a young age and suffer repeated infections. The prevalence of antibodies to the 27-kDa antigen was 2-to 3-fold higher for Haitian children Յ10 years of age (52 to 63%) (this work) than for U.S. children (21.3%) (21), and although the method of assay has varied between studies, similarly high seroprevalence values (40 to 100%) have been reported for children in other developing countries around the world (71,76,80). Incidence rates based on stool microscopy are also much higher among children in the developing world.…”
Section: Discussionmentioning
confidence: 54%